Simple Geometric Techniques to Delineate the Location, Extent, and Approximate Shapes of Attractors in Chaotic Systems - Choudhury, S. Roy (Journal of Applied Nonlinear Dynamics, 2026)
In this paper we examine the chaotic regimes of a variety of recently discovered hyperchaotic systems using a completely novel geometrical interpretation of the Competitive Modes analysis as simple criteria to map out the spatial location and extent, as well as the rough general shape, of the system attractor for any parameter sets corresponding to chaos. The accuracy of this mapping adds further evidence to the growing body of recent work on the correctness and usefulness of these Competitive Modes conjectures. Indeed, this may be taken as an ’a posteriori’ validation of the Competitive Modes conjectures.